2019
DOI: 10.1177/1758155919841279
|View full text |Cite
|
Sign up to set email alerts
|

Weak niche partitioning by migrating shorebirds in a single-food-type environment

Abstract: This study examined foraging niche partitioning among coexisting species of shorebirds on a sandy beach dominated by a single food type, Horseshoe Crab ( Limulus polyphemus) eggs, where use of foraging microhabitats of limited variety is temporarily restricted due to tidal cycle. The major goal of the study was to examine whether co-occurring species differed in selection of foraging microhabitats and use of feeding techniques. Ruddy Turnstone ( Arenaria interpres), Red Knot ( Calidris canutus), and Sanderling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Our study is consistent with previous research that suggested that among-species dietary niches tended to overlap more during seasons of high food abundance [32,33,125,126]. Greater resource availability could promote an increase in species utilization of similar resources and reduce competitive interactions between species [32,34,126]. By contrast, during seasons with low food abundance, species may partition limited food resources to decrease interspecific competition, leading to a decrease in niche overlap [126,127].…”
Section: Effects Of Tuber Collapse On Dietary Niche Breadth and Overlap Among Crane Speciessupporting
confidence: 91%
See 1 more Smart Citation
“…Our study is consistent with previous research that suggested that among-species dietary niches tended to overlap more during seasons of high food abundance [32,33,125,126]. Greater resource availability could promote an increase in species utilization of similar resources and reduce competitive interactions between species [32,34,126]. By contrast, during seasons with low food abundance, species may partition limited food resources to decrease interspecific competition, leading to a decrease in niche overlap [126,127].…”
Section: Effects Of Tuber Collapse On Dietary Niche Breadth and Overlap Among Crane Speciessupporting
confidence: 91%
“…The increased overlap may be related to the reduced competitive interaction between species due to great resource availability. For example, there was an absence of dietary niche partitioning among shorebird species at Delaware Bay, USA, when the density of their primary prey Horseshoe Crab eggs was high [ 34 ]. Extensive degree of dietary niche overlap has also been revealed among seabird species breeding on the Argentinean Patagonian coast with superabundance of pelagic fish [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many species (11) in our data set use a mixed pecking-probing strategy, which means shifting from sight to touch organ for prey detection. Eye closure seems a good indicator of the preeminent use of touch sense over visual stimuli.…”
Section: Cranial System and Food Capturementioning
confidence: 99%
“…A seminal interspecific comparative study introduced a classification of these foraging-feeding speciesspecific stereotyped behaviors [4]. This classification was subsequently used in numerous studies investigating the diet or the food acquisition behaviors of shorebirds (e.g., [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on shorebird foraging ecology in recent decades have been extensively conducted on species that have used wetlands along the American Flyways (Faria et al, 2018;Martínez-Curci et al, 2015;Novcic, 2019) and the African-Eurasian Flyway (Bocher et al, 2014;Lourenço et al, 2016Lourenço et al, , 2017. Among these studies, several have aimed to investigate the role of resource niche partitioning as a mechanism that maintains the diversity and stable coexistence of shorebird species within their communities.…”
Section: Introductionmentioning
confidence: 99%